Znaczenie ojca w wychowaniu dziecka w młodszym wieku szkolnym - Reczek-Zymróz , Łucja (Studia Edukacyjne, 2022)
The text addresses the relevance of fathers in the upbringing of children at an early age in an era of cultural and social change linked to globalization, medialization and technicization. The aim is to show what values modern fathers subscribe to, what role they play in the family and which areas of activity with children are their favorite. A total of 200 fathers of early school-age children participated in the survey (interview, conducted in Poland between 2018 and 2020.